Plasma procalcitonin levels in chronic haemodialysis patients - Akbulut, Handan; Çelik, Ilhami; Özden, Mehmet; Do?ukan, Ayhan; Bulut, Vedat (My University, 2005)
The objective of our study was to assess procalcitonin (PCT) and C-reactive protein (CRP) plasma concentrations in end-stage renal disease (ESRD) patients undergoing haemodialysis sessions and the effect of intermittent haemodialysis on PCT levels. We measured plasma PCT and CRP levels in 43 ESRD patients without evidence of systemic infection at the beginning of haemodialysis and 4 hours later. Control group consisted of 40 volunteers with no complaints. Venous blood samples were collected from the patient before and after hemodialysis and the control groups. PCT was assayed by immunoluminometry. The mean plasma concentration of PCT (2.13 ± 0.7 ng/mL) and CRP (14.3 ± 2.9 mg/L) was elevated prior to the start of the patients hemodialysis compared to healthy controls (PCT; 0.18 ± 0.03 ng/mL, CRP; 4.5 ± 2.2 mg/L) (P < 0.0001). After 4 h of haemodialysis, the levels of PCT decreased significantly (P > 0.05). In addition, a weak correlation between PCT and CRP before dialysis was established. It was found that PCT levels significantly increased in haemodialysis patients without signs of infection. This confirms the presence of a chronic systemic inflammatory state in these patients. Although haemodialysis was associated with a significant decrease of serum PCT, haemodialysis had no significant effect on CRP levels. © Tübi?tak.
Keywords: C-reactive protein; Haemodialysis; Procalcitonin